Functional profiles of children with cerebral palsy in Jordan based on the association between gross motor function and manual ability - Nihad A. Almasri; Maysoun Saleh; Sana Abu-Dahab; Somaya H. Malkawi; Eva Nordmark (BMC, 2018)
Abstract Background Cerebral palsy (CP) is the most common cause of physical disability in childhood. A major challenge for delivering effective services for children with CP is the heterogeneity of the medical condition. Categorizing children into homogeneous groups based on functional profiles is expected to improve service planning. The aims of this study were to (1) to describe functional profiles of children with CP based on the Gross Motor Function Classification System-Expanded & Revised (GMFCS-E & R) and the Manual Ability Classification System (MACS); and (2) to examine associations and agreements between the GMFCS-E & R and the MACS for all participants then for subgroups based on subtypes of CP and chronological age of children. Methods A convenience sample of 124 children with CP (mean age 4.5, SD 2.9 years, 56% male) participated in the study. Children were classified into the GMFCS-E & R and the MACS levels by research assistants based on parents input. Research assistants determined the subtypes of CP. Results Thirty six percent of the participants were able to ambulate independently (GMFCS-E & R levels I-II) and 64% were able to handle objects independently (MACS levels I-II). The most common functional profile of children with CP in our study is the "manual abilities better than gross motor function". An overall strong correlation was found between the GMFCS-E & R and the MACS (r s  = .73, p < .001), the correlations vary significantly based on subtypes of CP and chronological age of children. A very strong correlation was found in children with spastic quadriplegia (r s  = .81, p < .001), moderate with spastic diplegia (r s  = .64, p < .001), and weak with spastic hemiplegia (r s  = .37, p < .001). Conclusions The GMFCS- E & R and the MACS provide complementary but distinctive information related to mobility and manual abilities of children with CP. Subtypes of CP and chronological age differentiated functional profiles. Functional abilities of children with CP in Jordan have similar patterns to children with CP in other countries. Functional profiles can inform clinicians, researchers, and policy makers.